CORRELATION OF SANITATION WITH STUNTING IN MANDER VILLAGE, TAMBAKBOYO DISTRICT. TUBAN REGENCY - Aris Puji Utami; Suryo Ediyono; Ayu Setyorini (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2024)
Background: Stunting is one of the most critical malnutrition problems globally caused by multiple factors. Sanitation of the family environment, especially unhealthy ones, both from the criteria for housing, sanitation facilities owned and the behavior of household residents can increase the risk of stunting in toddlers. Objectives: This study aims to analyze the correlation between environmental sanitation and the incidence of stunting. Method: The study used a quantitative study with a correlational analytic research design, the population is all stunting in Mander Village, Tambakboyo District Tuban Regency in March 2024, as many as 42 toddlers were obtained by total sampling technique. Collecting data using a healthy home observation sheet and measuring height according to age, then the data was analyzed by using the Spearman Rank correlation test with a significance level of 0.05 Result: Most of respondent with unhealthy home environment sanitation as many as 28 respondents (66.6%), most of the toddlers experienced stunting in the short category as many as 23 toddlers (54.7%) and there was a significant relationship between sanitation and the incidence of stunting. stunting in children under five at the Mander Village, Tambakboyo District, Tuban Regency in 2023 (ρ value 0.001; r 0,725). Conclusion: There is a significant relationship between environmental sanitation and the incidence of stunting. Unhealthy home environment sanitation will increase the risk of children suffering from stunting greater than children from families with healthy home environment sanitation